Representasi Hukum pada Puisi Kesaksian Akhir Abad Karya W.S Rendra dan Lagu Mafia Hukum Karya Navicula - Zalfa, Zein Salsabila (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The study was intended to find out what legal representations are found in the poem by W.S. Rendra, entitled Kesaksian Akhir Abad and the song by Navicula, entitled Mafia Hukum. The theory used in this study is a generic structural theory, which examined a work of literature in relation to the world's social body of authors. The method used in this study is a qualitative descriptive method of research that is a method of research that utilizes qualitative data and described in a descriptive history. The source of the data used by the researcher is Kesaksian Akhir Abad by W.S. Rendra poem and the lyrics of Mafia Hukum song. In data collecting, researchers first collected research materials, reading and understanding the content of the poems of Kesaksian Akhir Abad to Navicula's Mafia Hukum song, then composed the legal elements therein. The data analysis technique in this study is the content analysis technique. Studies describe how Kesaksian Akhir Abad poems and lyrics of Mafia Hukum song have similarities and differences in response to Indonesian government systems.